Social and religious factors affecting Muslim-Christian relations - Michel, Thomas F. (Islam and Christian-Muslim relations, 1997)
The question of Christian‐Muslim relations can be approached in various ways. Historical studies have traced the shifts and changes in the place in society of Christians and other minority groups in the Middle East and Asia in general and in specific countries. Other studies have treated diplomatic relations between the Vatican and predominantly Muslim states or have analyzed, compared, and contrasted the policies of the churches on political issues such as the Palestine question and the state of Israel. Still other works have treated polemical and theological controversies between Muslims and Christians as well as efforts at dialogue and mutual understanding. In this paper, the focus is on the factors and issues that have affected Christian‐Muslim relations in the twentieth century, particularly in the Middle East and in Asia. I intend to approach the subject from the viewpoint of the religious and human relations between the communities of Christians and Muslims, outlining both the factors that favour positive living and working relations between the two communities, those that have raised tensions in the recent and more distant past, and those which present challenges yet to be resolved.